Contributions to the study of the genus Hephathus Ribaut, 1952 (Homoptera: Auchenorrhyncha: Cicadellidae: Macropsinae) of Russia and adjacent countries - Tishechkin, Dmitri Yu. (Zootaxa, 2015)
In Russia and the adjacent territories, the genus Hephathus includes three species, H. nanus (Herrich-Schäffer, 1835), H. freyi (Fieber, 1868) = H. tshakaranus Dlabola, 1957, syn. n., and H. achilleae Mityaev, 1967. They are indistinguishable in genitalia shape, but differ in male calling signal structure and black pattern of face. Photos of habitus and face, drawings of genitalia and male 2nd abdominal apodemes, signal oscillograms, and distribution maps for all species are provided. H. orientalis Linnavuori, 1953 is indistinguishable from H. freyi in coloration and genitalia shape; therefore, investigation of male calling signals is necessary for elucidation of its status. Macropsis fergusoni Evans, 1942 from Tasmania and Asmaropsis troilos Linnavuori, 1978 from Eritrea differ from Palaearctic Hephathus in the shape of head, pro-, and mesonotum and apparently belong to other genera.